1993
DOI: 10.1002/eji.1830230744
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐presenting cells in adoptively transferred and spontaneous autoimmune diabetes

Abstract: Histological techniques were used to identify antigen-presenting cells (APC) in adoptively transferred diabetes in NOD mice and Ins-HA transgenic mice, and in spontaneously diabetic NOD mice. In adoptively transferred disease, CD4+ T cells and F4/80+ macrophages dominated early infiltrates. By contrast, in spontaneously developing diabetes in NOD mice, lymphocytic infiltrates appeared to be well organized around a network of VCAM-1+ NLDC-145+ ICAM-1+ dendritic cells. Thus, the primary APC spontaneous autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
1
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 34 publications
5
50
1
1
Order By: Relevance
“…Dendritic cells have a pivotal role in initiating the immune response, due to their antigen-presenting function and their ability to provide accessory signals for T cell activation (29,30). Dendritic cells have been identified in target tissues of several autoimmune diseases, including rheumatoid arthritis (3 l), primary biliary cirrhosis (32), inflammatory vasculopathy of chronic allograft rejection (33), giant cell arteritis (9), and experimental autoimmune diabetes (34). As observed in our samples, these cells are usually detected in incipient inflammatory infiltrates and become rare in well-established or scarring lesions (9,31,33).…”
Section: Discussionsupporting
confidence: 51%
“…Dendritic cells have a pivotal role in initiating the immune response, due to their antigen-presenting function and their ability to provide accessory signals for T cell activation (29,30). Dendritic cells have been identified in target tissues of several autoimmune diseases, including rheumatoid arthritis (3 l), primary biliary cirrhosis (32), inflammatory vasculopathy of chronic allograft rejection (33), giant cell arteritis (9), and experimental autoimmune diabetes (34). As observed in our samples, these cells are usually detected in incipient inflammatory infiltrates and become rare in well-established or scarring lesions (9,31,33).…”
Section: Discussionsupporting
confidence: 51%
“…36 The mechanism by which CD8 ϩ T cells preferentially accumulated within the CNS is unclear, but the CNS itself must play a role shaping this response because initiation of CD4 ϩ T-cell responses does not lead to a disproportionate accumulation of CD8 ϩ T cells in other tissues. 37,38 For example, in our studies, a preferential accumulation of CD8 ϩ T cells was not observed when allogeneic dendritic cells were injected in the ear. Similarly, CD8 ϩ T cells accumulate only in relatively small numbers as compared with CD4 ϩ T cells during the initiation and progression of diabetes in a MHC-class-II-restricted TCR-transgenic model.…”
Section: Discussionmentioning
confidence: 46%
“…Different groups have provided evidence that betacell destruction can occur in the complete absence of antigen-specific contact between T cells and pancreatic beta cells [40,41,42]. Nevertheless, the experimental approaches and models used in those reports do not rule out a direct presentation of autoantigens to selfreactive CD4+ T cells by the beta cells themselves as an essential step in the pathogenesis of diabetes in humans and NOD mice.…”
Section: Discussionmentioning
confidence: 99%